EVALUATION OF DIURETIC ACTIVITY OF MUSSAENDA FRONDOSA - SREELAKSHMI R; SHAN P MOHAMMED; Harindran, Jyoti; P, Sriganesan (Asian Journal of Pharmaceutical and Clinical Research, 2015)
The present study deals with the evaluation of diuretic activityof the plant Mussaenda frondossa Linn. ,using Lipschitz method. Wistar albino rats was divided into 4 groups of 6 animals in each. Frusemide (20 mg/Kg p.o) used as a standard diuretics. Two doses of plant extract was used for the study. In urine the volume and concentration of electrolytes was measured at the end of 24 hrs. Result shows significant increase in diuretic activity. Keywords: Mussaenda frondosa, Lipchitz method, Alcoholic extract, Diuretic activity.